Navigating Reading Comprehension: Insights into Strategy Utilization and Cultural Influences among EFL Learners - Nurlaela Rahmawati; Dwi Nopiyadi; Aldha Williyan (National Conference on Language, Education, and Technology Proceeding, 2023)
Proficient reading comprehension is a fundamental pillar of language acquisition and academic excellence, empowering students to extract meaning from a diverse array of texts and nurturing essential critical thinking skills. This qualitative investigation delves into students' perceptions and utilization of reading strategies, employing comprehensive in-depth interviews and focused group discussions with tenth-grade high school students. Employing a phenomenological research framework, the study delves into how students actively employ a range of strategies, the rationale underlying their choice of specific techniques, and their evaluations of the efficacy of these strategies in bolstering reading comprehension. The findings underscore the dynamic nature of strategy preference and utilization among students. Participants exhibit a diverse spectrum of preferences, embracing strategies such as visualization, questioning, summarization, and forging connections based on their unique learning styles and contextual exigencies. These strategies emerge as cognitive tools that not only facilitate profound interaction with the text but also contribute to comprehension and the retention of knowledge. Remarkably, participants showcase metacognitive awareness, thoughtfully reflecting on their strategic decisions and adapting these strategies in consonance with the complexity of the text. The exploration further unveils the influence of cultural and linguistic factors on strategy selection. Participants hailing from various backgrounds emphasize how their cultural heritage and language proficiency mould their approach to reading. Additionally, discernible patterns in strategy preferences across demographic variables, including age, gender, and language proficiency, are identified, thereby offering nuanced insights into the interplay between personal attributes and strategic engagement. Ultimately, this research enriches our comprehension of reading comprehension strategies by illuminating the intricate interplay of individual characteristics, cultural contexts, and strategic deployment.